Risk and prognosis for brain metastasis in primary metastatic cervical cancer patients: A population-based study - Wu Jiao; Xu Qing; Huang Huixia; Pang Yangyang; Li Haoran; Cheng Xi (Open Medicine)
The purpose of this study was to evaluate the risk and prognostic factors of stage IVB cervical cancer with brain metastasis from a population-based database, the Surveillance, Epidemiology and End Results (SEER).